2022
DOI: 10.1038/s41467-022-32962-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated cohort of esophageal squamous cell cancer reveals genomic features underlying clinical characteristics

Abstract: Esophageal squamous cell cancer (ESCC) is the major pathologic type of esophageal cancer in Asian population. To systematically evaluate the mutational features underlying clinical characteristics, we establish the integrated dataset of ESCC-META that consists of 1930 ESCC genomes from 33 datasets. The data process pipelines lead to well homogeneity of this integrated cohort for further analysis. We identified 11 mutational signatures in ESCC, some of which are related to clinical features, and firstly detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…Two recent studies reported an integrative genomic analysis of a large cohort of published ESCC patients [31,32]. Zou et al reported the integrated reanalysis of the mutation data of WGS or WES from a total of 1145 tumor samples present in 7 large ESCC cohorts [31]. In 1145 ESCC patients, an average of 4.3 mutations/megabase was observed.…”
Section: Genomic Alterations Of Esccmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies reported an integrative genomic analysis of a large cohort of published ESCC patients [31,32]. Zou et al reported the integrated reanalysis of the mutation data of WGS or WES from a total of 1145 tumor samples present in 7 large ESCC cohorts [31]. In 1145 ESCC patients, an average of 4.3 mutations/megabase was observed.…”
Section: Genomic Alterations Of Esccmentioning
confidence: 99%
“…Using a cutoff of eight mutations/megabase to distinguish low tumor mutation burden (TMB) from high, it was shown that patients with high TMB have a lower OS compared with those with low TMB [31]. In the 7 cohorts of ESCC patients included in this analysis, 47 mutated genes were considered driver genes, but only 7 genes (TP53, NOTCH1, CDKN2A, ZNF50, NFE2L2, PIK3CA and RB1) were considered driver genes in the majority of studies; some genes, such as FAT1, FAT2, PTEN, EP300, FBXW7, APS31, MUC16 and RP&15, were considered driver genes only in a minority of studies [31]. Only the mutations of a few genes were correlated to clinical parameters, such as ZNF50 mutations related to lymph node metastasis [31].…”
Section: Genomic Alterations Of Esccmentioning
confidence: 99%
“…This requires not only sequencing a large number of patients to overcome its strong inter-tumoral heterogeneity, but also characterizing in detail the clonal makeup and evolution to decipher ESCC intra-tumoral heterogeneity. New research 4 , 5 published recently in Nature Communications have specifically taken on these two challenges, by performing genomic and epigenomic analyses with significant breadth and depth, and shed novel insights into ESCC tumor heterogeneity with translational implications.…”
mentioning
confidence: 99%
“…To address the inter-tumoral heterogeneity, Li et al 5 curated and integrated ESCC sequencing data from 1930 patients across 33 studies, representing one of the largest compendia of paired tumor-normal sequences. To ensure data quality and minimize batch effects, the authors paid extra attention and made efforts during quality control, data processing, homogenization and verification.…”
mentioning
confidence: 99%
See 1 more Smart Citation